All Days 2009
DOI: 10.2118/125043-ms
|View full text |Cite
|
Sign up to set email alerts
|

Practical Solutions for Pressure Transient Responses of Fractured Horizontal Wells in Unconventional Reservoirs

Abstract: This paper presents an analytical trilinear flow solution to simulate the pressure transient and production behavior of fractured horizontal wells in unconventional reservoirs (Ozkan et al., 2009). The model is simple, but versatile enough to incorporate the fundamental petrophysical characteristics of unconventional reservoirs, including the intrinsic properties of the matrix and the natural fractures. Special characteristics of fluid exchange among various reservoir components may also be considered. This pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(78 citation statements)
references
References 13 publications
0
77
0
1
Order By: Relevance
“…To validate the bottom hole pressure solution, we compared the solution with the classic dual-porosity trilinear flow model obtained from Brown et al (2009) for the special case of D f = 2, =0, =0 . The input data used for the comparison are listed in Fig.…”
Section: Validation and Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the bottom hole pressure solution, we compared the solution with the classic dual-porosity trilinear flow model obtained from Brown et al (2009) for the special case of D f = 2, =0, =0 . The input data used for the comparison are listed in Fig.…”
Section: Validation and Applicationmentioning
confidence: 99%
“…Similarly, Lee and Brockenbrough (1986) first proposed a trilinear flow model for a vertical well. The trilinear flow model was introduced into a fractured horizontal well by Brown et al (2009). They established a multi-fractured horizontal well model by treating the simulated area around hydraulic fracture stages as a dual-porosity medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major factors in determining the productivity index of the shale gas reservoir depends upon the fracture network (Brown et al 2009). In general, all the fractures are sourced by the matrix system.…”
Section: Back Ground Literaturementioning
confidence: 99%
“…Subsequently, the transition period becomes dominant, and finally late radial flow period is observed. Ozkan et al (2009) and Brown et al (2009) introduced the concept of trilinear flow for hydraulically fracture horizontal wells. They indicated that the contribution of micro-darcy formation beyond the stimulated volume is negligible and flow is mainly linear perpendicular to the hydraulic fracture.…”
Section: Introductionmentioning
confidence: 99%